The cult of King Charles the martyr - Lacey, Andrew, 1960- (Studies in modern British religious history, 2003)
The first study to deal exclusively with the cult ofKing Charles the Martyr - Charles I as suffering, innocent king, walking in the footsteps of his Saviour to his own Calvary at Whitehall - and the political theology underpinning it, taking the story up to 1859.